Cost-consciousness among Swiss doctors: a cross-sectional survey - Martin Diane P; Bovier Patrick A; Perneger Thomas V (BMC, 2005)
Abstract Background Knowing what influences physicians attitudes toward health care costs is an important matter, because most health care expenditures are the results of doctors' decisions. Many decisions regarding medical tests and treatments are influenced by factors other than the expected benefit to the patient, including the doctor's demographic characteristics and concerns about cost and income. Methods Doctors (n = 1184) in Geneva, Switzerland, answered questions about their cost-consciousness, practice patterns (medical specialty, public.vs. private sector, number of patients per week, time spent with a new patient), work satisfaction, and stress from uncertainty. General linear models were used to identify independent risk factors of higher cost-consciousness. Results Most doctors agreed that trying to contain costs was their responsibility ("agree" or "totally agree": 90%) and that they should take a more prominent role in limiting the use of unnecessary tests (92%); most disagreed that doctors are too busy to worry about costs (69%) and that the cost of health care is only important if the patient has to pay for it out-of-pocket (88%). In multivariate analyses, cost-consciousness was higher among doctors in the public sector, those who saw fewer patients per week, who were most tolerant of uncertainty, and who were most satisfied with their work. Conclusion Thus even in a setting with very high health care expenditures, doctors' stated cost-consciousness appeared to be generally high, even though it was not uniformly distributed among them.